Take your farm to town - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
The world is moving to the town and is taking its agriculture with it. Urban farmers will contribute even more to our future than they did to our past, but who will take responsibility for them 'This food is like a reserve. It helps when money is...